Achieving high energy storage properties in perovskite oxide via high-entropy design. Issue 8 (15th April 2023) - Ning, Yating; Pu, Yongping; Zhang, Qianwen; Zhou, Shiyu; Wu, Chunhui; Zhang, Lei; Shi, Yu; Sun, Zixiong
Abstract: In recent years, "high-entropy" materials have attracted great attention in various fields due to their unique design concepts and crystal structures. The definition of high-entropy is also more diverse, gradually expanding from a single phase with an equal molar ratio to a multi-phase with a non-equimolar ratio. This study selected (Na0.2 Bi0.2 Ba0.2 Sr0.2 Ca0.2 )TiO3 high entropy ceramics with excellent relaxation behavior. The A-site elements are divided into ( x  = Na, Bi, Ba) and ((1-3 x )/2 = Sr, Ca) according to their inherent properties. A novel ABO3 structural energy storage ceramics (NaBaBi) x (SrCa)(1-3 x )/2 TiO3 ( x  = 0.19, 0.195, 0.2, 0.205 and 0.21) was successfully fabricated using the high entropy design concept. The ferroelectric and dielectric properties of non-equimolar ratio high-entropy ceramics were studied in detail. It was found that the dielectric constant of ∼4920 and the recoverable energy storage density of 3.86 J/cm 3 (at 335 kV/cm) can be achieved simultaneously at x  = 0.205. The results indicate that the design concept of high-entropy materials with a non-equal molar ratio is an effective means to achieve distinguished energy storage performance in lead-free ceramics.